Logistics and Transport Competitiveness in Kyrgyzstan - United Nations Economic Commission for Europe (United Nations, 2020)
Improving the competitiveness of Kyrgyzstan as a transport logistics centre at the crossroads of Europe and Asia could enable the country to unlock significant untapped benefits of growing cargo flows between the two continents. This study identifies the transport infrastructure and services available in Kyrgyzstan, reviews the country’s extensive recent and future transport investments, and sets out recommendations to ensure its transport network is ready to harness the growth in inland transport from rising East-West trade, particularly in the context of the Belt and Road Initiative, within which Kyrgyzstan could occupy a strategic geographical position. To further capitalize on Kyrgyzstan’s pivotal role in Euro-Asian transport logistics, this study also presents the benefits of adhering to and implementing the full spectrum of UN Transport Conventions and Legal Instruments administered by UNECE, and through its continued participation in UNECE initiatives such as the Euro-Asian Transport Links project. The study also highlights strengthening the harmonization of legislation as one of the most important conditions for the development of the transport infrastructure of Kyrgyzstan and the broader region, of which Kyrgyzstan is a member.